2011
DOI: 10.1002/cvde.201006881
|View full text |Cite
|
Sign up to set email alerts
|

MOCVD of Vertically Aligned ZnO Nanowires Using Bidentate Ether Adducts of Dimethylzinc

Abstract: The dimethylzinc-bidentate ether adducts [Me 2 Zn(1,4-dioxane)] (1), [Me 2 Zn(1,2-dimethoxyethane)] (2) and [Me 2 Zn(1,4-thioxane)] (3) are used as precursors for the growth of vertically aligned zinc oxide (ZnO) nanowires (NWs) by liquid-injection, metal-organic (MO)CVD. The ZnO NWs are deposited on Si(111) and F-doped SnO 2 /glass substrates in the absence of a seed catalyst. The precursors (1) and (2) are used to deposit ZnO NWs at substrate temperatures of 450 8C and 500 8C, whilst higher deposition temper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 76 publications
0
18
0
Order By: Relevance
“…Generally, the vapor phase synthesis process is carried out at higher temperatures from 500 • C to 1500 • C and produces high-quality nanowires. The typical vapor phase synthesis method includes vapor liquid solid (VLS) growth [47], chemical vapor deposition (CVD) [48], metal organic chemical vapor deposition (MOCVD) [49], physical vapor deposition (PVD) [50], molecular beam epitaxy (MBE) [51], pulsed laser deposition (PLD) [52], and metal organic vapor phase epitaxy (MOVPE) [53]. Among the vapor phase synthesis methods, VLS and MOCVD are two of the most important methods for the ZnO nanowires synthesis.…”
Section: The Vapor Phase Synthesismentioning
confidence: 99%
“…Generally, the vapor phase synthesis process is carried out at higher temperatures from 500 • C to 1500 • C and produces high-quality nanowires. The typical vapor phase synthesis method includes vapor liquid solid (VLS) growth [47], chemical vapor deposition (CVD) [48], metal organic chemical vapor deposition (MOCVD) [49], physical vapor deposition (PVD) [50], molecular beam epitaxy (MBE) [51], pulsed laser deposition (PLD) [52], and metal organic vapor phase epitaxy (MOVPE) [53]. Among the vapor phase synthesis methods, VLS and MOCVD are two of the most important methods for the ZnO nanowires synthesis.…”
Section: The Vapor Phase Synthesismentioning
confidence: 99%
“…−28 °C, b.p. 118 °C), which are moderately soft Lewis acids that form adducts with a variety of ligands 10. Structural studies of the gas phase have revealed a linear coordination mode 11.…”
mentioning
confidence: 99%
“…4, together with significant bond lengths and angles. Full crystallographic and structural data for [Me 2 Zn(1,4-dioxane)] will be published elsewhere [28]. In the absence of X-ray crystallographic data [Me 2 Zn(1,4-dioxane)] was originally proposed to be a monomeric molecule with a bidentate chelating 1,4-dioxane ligand [22].…”
Section: Resultsmentioning
confidence: 99%